Respon Bibit Kakao terhadap Pemberian Pupuk Organik Limbah Cair Pabrik Kelapa Sawit dan Dolomit pada Tanah Sulfat Masam - Ida Nursanti; Araz Meilin (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
Acid sulfate soil productivity is low due to the low availability of nutrients and high levels of soil acidity. It needs the organic material and dolomite to create the growing medium to be balance on its nutrient available, both physical and biological characteristic on the acid sulfated land. The aim of this research was to know the respond of cacao germ and the optimal doses of organic fertilizer of palm oil mill effluent. This research was take place in Jambi during September 2012 until March 2013. The factorial completely randomized design was applied. The first factor was organic fertilizer of palm oil mill effluent doses (0, 70, 140 and 280 ml.polybag-1 or equivalent with 0, 28.000, 56.000 and 84.000 l.ha-1). The second factor was dolomit doses (0, 2 and 4 g.polybag-1 or equivalent with 0, 800 and 1600 kg.ha-1). Kakao Lindak Klon ICS 13 was used as indicator plant. The acid sulfated soil was taken from Lagan Ulu Village Tanjung Jabung Timur District Jambi Province. The result of the research showed that the respond of cacao germ toward to an organic fertilizer of palm oil mill effluent and dolomite useness effected on the increasing of vegetative growth. Generally conclusions showed that the combination of 800 kg.ha-1 of dolomite and 84.000 l.ha-1 organic fertilizer of palm oil mill effluent was the optimal treatment which show the maximum of plant high, crown dry weigh, leaf wide and root crown ratio.